Characterization of the negativism, activation, self-confidence and cognitive orientations levels of alpinists - Ana Dalila Rodrigues; João Paulo Lázaro; Helder Miguel Fernandes; José Vasconcelos-Raposo (Desafio Singular, 2009)
The present study aims to characterize the levels of negativism, activation, self-confidence and cognitive orientation of different mountain sports' participants, taking into account various variables (i.e. gender; age; years of experience; nationality; training and, specific sport). The sample was composed of 45 participants (40 male and 5 female) with an age range between 20 and 61 years of age (M=33,91; SD=8,97), who completed the Portuguese or English version of the CSAI-2 and TEOSQ questionnaires, according to their linguistic proficiency. The main results revealed that the variable 'years of experience' (and not age) correlated positively with the levels of self-confidence and task orientation. On the other hand, but in accordance with postulated theories, it was verified a positive association between the levels of negativism and ego orientation. Due to the relatively few studies done until today on this thematic and this type of samples, the results were discussed in relation to the respective theoretical models and specificities of this sport.